Axial behavior of circular steel tube with localized penetrating corrosion simulated by artificial notch. (March 2022) - Gao, Shan; Wang, Yulin; Guo, Lanhui; Xu, Youchun; Iyama, Jun
Abstract: Aiming to assess the compressive performance degradation of circular steel tube with localized penetrating corrosion, 26 specimens with artificial notch were tested by considering the corrosion type, corrosion length and corrosion orientation. The experimental results indicated that notch orientation shows the most remarkable effect on the failure model of the tubes. The close of crack notch which would result in the double peak in the load–displacement curve is beneficial for the post-buckling behavior of the tubes. Decreasing the orientation angle of notch would increase the reduction in the compressive resistance of the tubes whilst the type of hole notch is much more favorable than crack notch. Based on the test results, the reduction factors for the compressive resistance of circular short steel tubes with slim localized penetrating corrosion are described by a semi-empirical formula. The parametric analysis confirms that the proposed design formula predicts the compressive resistance of the circular tube with slim localized penetrating corrosion well. Highlights: 26 circular steel tubes with localized penetrating corrosion were loaded axially. Notch orientation shows the most remarkable effect on the failure model of the tubes. The type of hole notch is much more favorable than crack notch under the same corrosion area. Reduction factor for the compressive strength of circular tube with local penetrating corrosion is proposed.